The Relationship between Exclusive Breastfeeding and Stunting Incidents in Candipuro Village - Erika Puspitasari; Sri Wahyunigsih; Agustina Widayati; Sunanto (KHD Production, 2023)
Stunting is a problem of chronic malnutrition caused by a lack of nutrition for a long time, resulting in growth disorders. The condition of inadequate nutritional intake in children is important for stunting. The best nutritional intake for babies is breast milk. Breastfeeding is thought to affect the incidence of stunting. This study aimed to determine the relationship between exclusive breastfeeding and the incidence of stunting in Candipuro Village. The research design uses qualitative research, namely retrospective or case-control. The sampling technique used in this study is purposive sampling. Analysis of the data used in this study is to use descriptive and bivariate data analysis. The Chi-square data analysis results show a relationship between exclusive breastfeeding and the incidence of stunting in Candipuro Village (p=0.00). Thus, it can be concluded that there is a relationship between exclusive breastfeeding and the incidence of stunting in Candipuro Village. The results of this study provide input for mothers to provide exclusive breastfeeding to infants to avoid stunting.